Women’s Ministry in the Javanese Christian Church in Feminist Ecclesiology - Ayu Wijayanti, Nona Kharisma; Harisantoso, Imanuel Teguh (TELEIOS: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
Abstract: The oppression of women who are considered trivial, low, and weak occurs in society, especially the church, which should apply God's love in its life. The patriarchal culture that is still inherent in the church order system is an important thing that needs to be highlighted. Oppressed and excluded women should get the same or equal rights as men. This research aims to create novelty and contribute to the academic world. To respond to this, the researcher researched the position of women in church services, especially in the cultural context of the Javanese Christian Church.  The understanding and role of feminist ecclesiology needs to be created in the context of ministry, especially in the Javanese Christian Church. The research method used is a qualitative method to support this research. In the context of Indonesia, especially in Javanese culture, patriarchal culture still exists today. Women often get an underestimated place in everything. In various aspects, women often get the last position, especially in the field of service in the Church.  This article aims to analyze women's ministry in the Javanese Christian Church from the perspective of feminist ecclesiology.